Mitral valve endocarditis caused by Pseudomonas aeruginosa: a case report - Polovina, Marija; Potpara, Tatjana; Milosevic, Ivana; Stepanovic, Jelena; Jovanovic, Momcilo; Pavlovic, Milorad (The Journal of Infection in Developing Countries, 2014)
Previously, endocarditis caused by Pseudomonas aeruginosa mostly involved right-sided valvular infection and generally carried a good prognosis. Recently, changes have been observed in the occurrence and clinical presentation of pseudomonal endocarditis, with increasing incidence of nosocomial infections and involvement of the aortic and mitral valves. Still, pseudomonal left-sided endocarditis is rare, but is frequently associated with complications and high mortality rates. A case of a high-risk patient with coronary artery disease and left-ventricular dysfunction, successfully treated for pseudomonal mitral valve endocarditis complicated by splenic abscess formation, is presented here.